2013
DOI: 10.1021/ic4007636
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Synthetic Method and Annealing Temperature on Metal Site Preference in Al1–xGaxFeO3

Abstract: Magnetoelectric materials couple both magnetic and electronic properties, making them attractive for use in multifunctional devices. The magnetoelectric AFeO3 compounds (Pna2(1); A = Al, Ga) have received attention as the properties of the system depend on composition as well as the synthetic method used. Al(1-x)Ga(x)FeO3. (0 ≤ x ≤ 1) was synthesized by the sol-gel and coprecipitation methods and studied by X-ray absorption near-edge spectroscopy (XANES). Al L(2,3-), Ga K-, and Fe K-edge XANES spectra were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It was established that XANES is sensitive to oxygen vacancies and bond covalency in several pyrochlore systems. [24][25][26] It was generally found that Zr and Hf cation coordination number (CN) increases with increasing size of the Ln cation as the pyrochlore approaches the phase boundary. The change in the CN tends to reflect an increase in local disorder across the pyrochlore series.…”
Section: Introductionmentioning
confidence: 99%
“…It was established that XANES is sensitive to oxygen vacancies and bond covalency in several pyrochlore systems. [24][25][26] It was generally found that Zr and Hf cation coordination number (CN) increases with increasing size of the Ln cation as the pyrochlore approaches the phase boundary. The change in the CN tends to reflect an increase in local disorder across the pyrochlore series.…”
Section: Introductionmentioning
confidence: 99%
“…The starting binary oxides used in the ceramic route had defined crystal structures, which likely acted as a template, increasing the ordering between the metal-oxygen polyhedra. 56 In contrast, the starting precipitate materials that were formed in the co-precipitation method lacked this inherent structure. This explains why the lattice constants of the materials made via the ceramic method were greater than those of the materials made via the co-precipitation route.…”
Section: Powder Xrdmentioning
confidence: 99%
“…For example, Walker and Grosvenor investigated the Al 1−x Ga x FeO 3 (0 ≤ x ≤ 1) system synthesized through sol−gel, coprecipitation, and ceramic methods. 13 They observed through X-ray absorption near-edge spectroscopy measurements that samples synthesized by the coprecipitation method revealed the largest variability in the metal coordination number depending on the composition and annealing temperature. The coordination number changes were also observed with the sol−gel and ceramic methods but to a much smaller extent.…”
mentioning
confidence: 99%
“…In other words, does changing how a material is made change its properties? For example, Walker and Grosvenor investigated the Al 1– x Ga x FeO 3 (0 ≤ x ≤ 1) system synthesized through sol–gel, coprecipitation, and ceramic methods . They observed through X-ray absorption near-edge spectroscopy measurements that samples synthesized by the coprecipitation method revealed the largest variability in the metal coordination number depending on the composition and annealing temperature.…”
mentioning
confidence: 99%